2019
DOI: 10.1080/02670836.2019.1572316
|View full text |Cite
|
Sign up to set email alerts
|

Austenite stabilisation by two step partitioning of manganese and carbon in a Mn-TRIP steel

Abstract: In addition to manganese, carbon partitioning has been proposed in a new medium Mn-TRIP steel by two-step partitioning during the first batching annealing and the final continuous annealing. In the second-step partitioning, the cementite dissolves and blocky austenite forms with carbon enrichment, while the partition of manganese is negligible from prior lath austenite back into ferrite due to short duration. The combined partition of carbon and manganese improves both fraction and stability of retained austen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Medium Mn steels containing 5-10 wt% Mn have been listed as one of the third-generation advanced high-strength steels for automobile application due to their attractive combination of strength and plasticity [1][2][3][4][5][6][7][8][9]. The superior mechanical properties are mainly originated from the transformation of metastable austenite into hard martensite during deformation, namely the transformation-induced plasticity (TRIP) effect [4,7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Medium Mn steels containing 5-10 wt% Mn have been listed as one of the third-generation advanced high-strength steels for automobile application due to their attractive combination of strength and plasticity [1][2][3][4][5][6][7][8][9]. The superior mechanical properties are mainly originated from the transformation of metastable austenite into hard martensite during deformation, namely the transformation-induced plasticity (TRIP) effect [4,7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Medium Mn steels containing 5-10 wt% Mn have been listed as one of the third-generation advanced high-strength steels for automobile application due to their attractive combination of strength and plasticity [1][2][3][4][5][6][7][8][9]. The superior mechanical properties are mainly originated from the transformation of metastable austenite into hard martensite during deformation, namely the transformation-induced plasticity (TRIP) effect [4,7,[10][11][12][13]. In general, the volume fraction of 20% to 50% metastable austenite is retained in the final microstructure of medium Mn steels, which is greater than that of the conventional TRIP-assisted steels [2,[4][5][6]9,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [11] reported that during aging treatment, layered reverted austenites will be formed. As the reverted austenite can reduce the {111} fiber in martensite [12] and prevent the crack propagation during tensile deformation, the ductility of maraging steels will be improved [13,14]. However, the content of reverted austenites cannot be easily controlled so that the toughening (ductility improvement) effect is unstable.…”
Section: Introductionmentioning
confidence: 99%